THE EFFECT OF AUDITORY INTELLECTUALLY REPETITION (AIR) LEARNING MODEL ON LEARNING OUTCOMES OF STUDENTS CLASS X OFFICE MANAGEMENT - Desita Ramadani; Siti Sri Wulandari (Jurnal Pendidikan Ilmu Sosial, 2023)
This research is motivated by the large number of student learning outcomes in the Basic - Basic Office Management and Business Services subjects which have not yet achieved the completeness score given by the teacher teaching these subjects. In addition, after conducting preliminary studies and observations at SMKN 1 Lamongan in class X MP 1 and 2 they tend to be passive because the learning model delivered still often uses a teacher-centered learning model using the lecture method. Thus, there is a need for learning innovation to make students more active in teaching and learning activities. The purpose of this study was to determine whether there were differences in student learning outcomes using the Auditory, Intellectually Repetition (AIR) learning model in the Basics of Office Management and Business Services in class X MP 1 and 2 at SMKN 1 Lamongan. This type of research uses experimental research. The design of this experimental research is Quasi Experimental Design, the type of quasi experimental design used is Nonequivalent Control Group Design. The subjects of this study were students of class X MP 1 as the control class, and students of class X MP 2 as the experimental class. Data collection techniques used documentation, observation, tests and research instruments in the form of pretest and posttest learning outcomes test sheets. The results showed that ttest 0.05, namely 0.000 0.05 and tcount 6.140 ttable 1.994. In these results it is known that Hα is accepted and H0 is rejected. The significant increase in learning outcomes in the experimental class was 19.71 while in the control class there was an increase in learning outcomes of 11.94. So it can be concluded that there are differences in student learning outcomes using the Auditory, Intellectually Repetition (AIR) learning model which is applied to the Basics of Office Management and Business Services in class X MP SMKN 1 Lamongan.